COVID-19 pandemic stressors and their longer-term association with young people’s wellbeing - James Laurence; Emer Smyth (PLoS ONE, 2026)
There is a significant body of research on adolescent wellbeing during the pandemic but less attention to the pathways through which the pandemic might be driving longer-term impacts on wellbeing. This paper addresses this gap using prospective cohort data collected at three time-points (ages 9, 12, 13; n = 2404; 50% female; 12.3% migrant-background) in Ireland, a country with a protracted period of school closures. Data collected from mid-2021 to mid-2022 (the late- to post-pandemic period) are used to analyse whether disruption across key domains such as education, family and peer relations during the pandemic has longer-term associations with adolescent self-reported mental wellbeing, while adjusting for socioemotional wellbeing before and during the pandemic. Several stressors (e.g., health-anxiety, support for home learning), which predicted worse wellbeing during the pandemic, were not significantly associated with late-/post-pandemic wellbeing. However, adolescents who, at the height of the pandemic, experienced greater disruption to familial relations and peer social relations (especially among girls), household economic shocks, elevated screen-time use, and a lack of a quiet place to study, report worse longer-term wellbeing outcomes. Some of these longer-term associations emerge from their link with worse wellbeing reported during the pandemic, which, in turn, predicts poorer longer-term wellbeing. However, screen-time and economic shocks remain linked with poorer late-/post-pandemic wellbeing even after accounting for peri-pandemic wellbeing. The findings highlight how external shocks such as the pandemic appear to be experienced differently depending on the social and economic resources of young people and their families, and how these can potentially shape adolescents’ wellbeing after the initial stressors have abated.